Prevalência de cárie precoce da infância em escolas municipais da cidade de Araçatuba - Corado, Carolyne [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Early childhood caries (CPI) is considered as a public health problem affecting young children in developing countries. The evolution of the CPI can lead to destruction of the primary dentition and therefore disorders in the development of the stomatognathic system and social/psychological problems that affect the child's quality of life. The aim of this study was to determine the prevalence of dental caries in children aged 3 to 6 years of age and promote educational and preventive actions in public schools in the city of Araçatuba - SP. After approval of those responsible, intraoral clinical examination was conductedin 410 children between 3 and 6 years, under natural light, with the help of wooden spatulas and gauzes of age, in 10 preschools (EMEIs) of Araçatuba. The children were classified into four groups: caries free (LC), active white spot (MB), early childhood caries (CPI) and severe childhood caries (CSI). The data obtained from oral conditions were evaluated according to gender and age of the children and submitted to statistical analysis. Preventive-educational activities were held at the school consisted of oral hygiene instructions and supervised toothbrushing in children, and playful activities with oral health theme. The results showed that the children had a mean of 60.82 months of age and that there was an homogeneous distribution between genders. 71.2% of the population evaluated was caries free and 28.8% of the population presented some initial sign of dental caries. These children with carious lesions, 5.9% had CSI, 18,8% had CPI and 4.1% active MB. There was an increase in the percentage of children affected with caries (white spot and cavities) after 61 months of age. We conclude that the prevalence of caries in young children in Araçatuba is considered high, higher than the national average (26,7%) for age, requiring...

A cárie precoce da infância (CPI) apresenta-se como um problema de saúde pública afetando crianças jovens em países em desenvolvimento. A evolução da CPI pode levar a destruição da dentição decídua e consequentemente a transtornos no desenvolvimento do sistema estomatognático, desordens sociais e psicológicas que afetam a qualidade de vida da criança. O objetivo deste estudo foi verificar a prevalência de cárie precoce da infância e promover ações educativo-preventivas em escolas públicas do município de Araçatuba - SP. Após a aprovação dos responsáveis, foi realizado o exame clínico intrabucal em 410 crianças entre 3 e 6 anos de idade, sob luz natural, com o auxílio de espátulas de madeira e gazes, em 10 escolas (EMEIs) de Araçatuba. As crianças foram classificadas em quatro grupos: livres de cárie (LC), mancha branca ativa (MB), cárie precoce da infância (CPI) e cárie severa da infância (CSI). Os dados das condições bucais obtidos foram avaliados de acordo com o gênero e a idade das crianças e submetidos à análise estatística. Ações preventivo-educativas foram realizadas nas escolas que consistiram em instruções de higiene oral e escovação supervisionada nas crianças, além de ações lúdicas com tema de saúde bucal. Os resultados mostraram que as crianças apresentaram média de 60,82 meses de idade e que houve uma distribuição homogênea entre os gêneros. 71,2% da população avaliada apresentavam-se livre de cárie e 28,8% da população com algum sinal de lesão de cárie. Dessas crianças com lesões de cárie, 5,9% apresentavam CSI, 18,8% apresentavam CPI e 4,1% com MB ativa. Houve um aumento na porcentagem de crianças afetadas com lesões de cárie após 61 meses de idade. Conclui-se que a prevalência de cárie precoce da infância em Araçatuba é considerada alta, maior que a média nacional (26,7%) para a idade, sendo...
Keywords: Araçatuba (SP); Cárie dentária; Criança; Dentes decíduos; Dental caries